Faith Communities and Breast/Cervical Cancer Prevention: Results of a Rural Alabama Survey - Linda L. Dunn; JoAnn Oliver; Margaret A. Lyons (Rural Nurse Organization; Binghamton University, 2005)
Limited research has been conducted in the area of faith-based health promotion programs. Data reported here are from a survey of faith communities in Walker County, Alabama for the following purposes: 1. To ascertain if breast and/or cervical cancer education was being offered by faith communities in Walker County, Alabama; 2. If so, what opportunities do faith communities provide; 3. To identify barriers that might inhibit the offering of breast/cervical cancer education to women in Walker County, Alabama; and 4. To determine the willingness of faith communities to meet with researchers to explore the option of providing breast/cervical cancer education to their faith communities. A survey was sent to 218 faith communities that were listed in the Daily Mountain Eagle (Walker County newspaper). A total of 46 surveys were returned, for a response rate of 25%. Data were analyzed using SPSS 11.0 for Windows. Researchers with qualitative expertise conducted the content analysis. Less than 1% of the faith communities reported any involvement in breast/cervical cancer education. Barriers to offering breast/cervical cancer education included a lack of financial resources and a lack of clergy/spiritual leaders with experience in providing breast/cervical cancer education. In addition, breast/cervical cancer education was not seen as part of the faith community's mission. Ministers cited a lack of community resources and a personal lack of knowledge about breast/cervical cancer as reasons for not providing health promotion activities in this area. Ninety-nine percent (99%) stated that they would be willing to meet with the researchers to plan breast/cervical cancer education. One percent (1%) stated that such informational offerings would not be necessary.